Taking the next step: Improving care transitions from a first‐episode psychosis service. Issue 1 (8th February 2021) - Gallagher, Keith; Ferrara, Maria; Pollard, Jessica; Yoviene Sykes, Laura; Li, Fangyong; Imetovski, Shannon; Cahill, John; Mathis, Walter; Srihari, Vinod H.
Abstract: Aims: First‐episode services (FES) improve outcomes in recent onset psychosis, but there is growing concern about how patients fare after discharge from these time‐limited services. Methods: A quality improvement approach (QI) was used to improve patient engagement in the discharge planning process (disposition), and successful engagement in care 3 months after discharge from the FES (transfer). Data from 144 consecutive discharges over 62 months are presented. A planning phase was followed by recurrent Plan‐Do‐Study‐Act cycles (PDSA) that included the introduction of proactive efforts targeting disposition planning (with patients and families) and follow‐up to facilitate transfer after discharge. Fisher's exact test was used to compare disposition and transfer outcomes across the QI phases. Results: This QI approach was sustained through a three‐fold escalation in discharge volume. Transfer status at 3 months was significantly different between the pre‐ and post PDSA phases ( p  = .02). A greater proportion were confirmed transfers post‐PDSA (54.3 vs. 37%), but of those with known status at 3 months, similar proportions were successfully transferred (76, 73%). Patients discharged post‐PDSA were less likely to have unknown treatment status (26 vs. 51%). Disposition outcomes were also significantly improved post‐PDSA ( p  = .03). Patients were more likely to engage with discharge planning (69.7 vs. 48.6%) and less likely to be lost to follow‐up (13.8 vs. 25.7%), or to refuse assistance (11.0 vs. 20.0%). Conclusion: This QI approach offers a feasible way to improve disposition and transfer after FES and can be built upon in efforts to sustain functional gains in onward pathways.